2017
DOI: 10.1371/journal.pone.0175335
|View full text |Cite
|
Sign up to set email alerts
|

Association between different anticholinergic drugs and subsequent dementia risk in patients with diabetes mellitus

Abstract: BackgroundThe effects of oxybutynin, solifenacin and tolterodine on dementia risk in patients with diabetes mellitus (DM) remain unknown. We investigated the effects of oxybutynin, solifenacin and tolterodine on dementia risk in patients with DM.MethodsWe conducted a cohort study by using the diabetes dataset of the Taiwan National Health Insurance Research Database from 1 January, 2002 to 31 December, 2013. We included 10,938 patients received one type of oxybutynin, solifenacin, or tolterodine, while 564,733… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
0
21
1
Order By: Relevance
“…Several previous studies have reported the association between antidepressant usage and the risk factor for dementia (Lee et al, 2016;Then et al, 2017); nevertheless, our study revealed no such association between antidepressants with anticholinergic effects (most tricyclic antidepressants) and the risk of dementia. In addition, one study using the NHIRD database reported the association between antimuscarinics for an overactive bladder (OAB) and the subsequent dementia risk in patients with diabetes mellitus (Yang et al, 2017). However, in our study, the usage of urological drugs (antimuscarinics, such as oxybutynin, solifenacin, and tolterodine) was not associated with the risk of dementia.…”
Section: The Different Types Of Anticholinergic Medications and Theircontrasting
confidence: 73%
“…Several previous studies have reported the association between antidepressant usage and the risk factor for dementia (Lee et al, 2016;Then et al, 2017); nevertheless, our study revealed no such association between antidepressants with anticholinergic effects (most tricyclic antidepressants) and the risk of dementia. In addition, one study using the NHIRD database reported the association between antimuscarinics for an overactive bladder (OAB) and the subsequent dementia risk in patients with diabetes mellitus (Yang et al, 2017). However, in our study, the usage of urological drugs (antimuscarinics, such as oxybutynin, solifenacin, and tolterodine) was not associated with the risk of dementia.…”
Section: The Different Types Of Anticholinergic Medications and Theircontrasting
confidence: 73%
“…Some studies reported an increasing dementia risk with greater exposure to anticholinergic drugs, consistent with a causal link [ 9 , 10 , 26 ]. However, few studies excluded drug exposure in the period just prior to dementia [ 9 , 10 , 41 ], and so drugs may have been prescribed for early symptoms of dementia. Two large UK studies report differences in dementia risk according to anticholinergic drug class, inconsistent with a causal link [ 9 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies independently exploring the effects of anticholinergic burden and gabapentin on cognition found limited evidence of adverse reactions relating to the use of these medications in patients with SCI [44,45]. These results are in contrast to a sizable body of evidence of negative associations between anticholinergic medication-use and cognitive impairment in able-bodied individuals [62][63][64][65][66] and individuals comprising other illness samples [67][68][69][70][71], and may relate to inadequate length of follow-up, insufficient statistical power to detect effects, and/or use of measures that lack sensitivity to detect cognitive decline.…”
Section: Introductionmentioning
confidence: 99%